2016
DOI: 10.3389/fimmu.2016.00190
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Exposed Uninfected Infants in Zimbabwe: Insights into Health Outcomes in the Pre-Antiretroviral Therapy Era

Abstract: The ZVITAMBO trial recruited 14,110 mother–infant pairs to a randomized controlled trial of vitamin A between 1997 and 2000, before the availability of antiretroviral therapy for HIV prophylaxis or treatment in Zimbabwe. The HIV status of mothers and infants was well characterized through 1–2 years of follow-up, leading to the largest cohort to date of HIV-exposed uninfected (HEU) infants (n = 3135), with a suitable comparison group of HIV-unexposed infants (n = 9510). Here, we draw on 10 years of published fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
72
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 113 publications
6
72
0
1
Order By: Relevance
“…Among the HIV-exposed children in ZVITAMBO, inflammatory markers (e.g., C-reactive protein and α-acid glycoprotein) were associated with stunting (26). Similarly, Evans et al (29) found that immune activation and inflammation are likely key drivers of postnatal growth failure among HEU compared with unexposed children. It is possible that stunting may play a stronger mediating role between SGA and postneonatal mortality among HIV-exposed immunocompromised children than among HIV-unexposed children.…”
Section: Discussionmentioning
confidence: 92%
“…Among the HIV-exposed children in ZVITAMBO, inflammatory markers (e.g., C-reactive protein and α-acid glycoprotein) were associated with stunting (26). Similarly, Evans et al (29) found that immune activation and inflammation are likely key drivers of postnatal growth failure among HEU compared with unexposed children. It is possible that stunting may play a stronger mediating role between SGA and postneonatal mortality among HIV-exposed immunocompromised children than among HIV-unexposed children.…”
Section: Discussionmentioning
confidence: 92%
“…There is evidence suggesting that exposure to HIV‐1 in utero , intrapartum, and during breastfeeding may confer a high risk of mortality, morbidity, and growth retardation in children, even in the absence of HIV‐1 transmission . Evans et al suggested that the potential underlying causes of morbidity and mortality in HEU children centered around fetal immune activation and immunological abnormalities resulting from direct exposure to HIV‐1 in utero .…”
mentioning
confidence: 99%
“…In 2016 alone, more than one million HEU infants were born (Slogrove et al, 2018). HEU infants are born with lower birthweight and shorter length compared with HIV-unexposed uninfected infants (Bailey, Kamenga, Nsuami, Nieburg, & St Louis, 1999;Evans, Humphrey, Ntozini, & Prendergast, 2016;Kurewa et al, 2009;Marinda et al, 2007;Patel et al, 2010;Sofeu et al, 2014;Taha et al, 1995) and experience high rates of stunting within the first five years (Bailey et al, 1999;Bobat, Coovadia, Moodley, Coutsoudis, & Gouws, 2001;McGrath et al, 2012;Newell, Borja, & Peckham, 2003;Patel et al, 2010).…”
mentioning
confidence: 99%